Maeve Kelly: Women, Ireland, and the Aesthetics of Radical Writing. Issue 2 (November 2019) - Workman, Simon
Abstract : This article considers the work of Irish writer and feminist Maeve Kelly arguing that she has been not only a radical and, to some extent, seminal voice within modern Irish writing, but an author whose work self-consciously reflects upon the production and mediation of Irish women's writing within British and Irish culture. While Kelly is not unique in adopting a feminist approach in her writing, aspects of her fiction are somewhat discrete within modern Irish literature in terms of how they express, delineate, and resolve the challenges – material, psycho-cultural, aesthetic – attendant upon the representation of feminist political thought and occluded Irish female experience. Particularly within an Irish context, Kelly's writing provides a significant case study of the aesthetic problematics of politically radical fiction. Her oeuvre represents a vital contribution to Irish writing of the twentieth century as well as to the history of women in post-war Ireland.